Design, synthesis, and biological evaluation of (E)-2-benzylidene-1-indanones derivatized by bioisosteric replacement of aurones - Youngshim Lee; Seunghyun Ahn; Euitaek Jung; Dongsoo Koh; Yoongho Lim; Young Han Lee; Soon Young Shin (Applied Biological Chemistry)
Abstract Thymic stromal lymphopoietin (TSLP) is a cytokine derived from epithelial cells and plays an essential role in the onset and activation of Th2-derived allergic inflammatory conditions, including atopic dermatitis. Despite their potential as drug targets, well-defined small molecules that effectively block TSLP expression are still lacking. A plant-derived secondary metabolite, aurone, was derivatized based on bioisosteric replacement to identify compounds that inhibit the promoter activity of TSLP. Thirteen (E)-2-benzylidene-1-indanones were designed and synthesized, and their structures were identified using NMR spectroscopy and mass spectrometry. Inhibition of the expression of TSLP triggered by interleukin-4 (IL-4) caused by (E)-2-benzylidene-1-indanones was measured using a TSLP gene promoter-reporter activity assay. Because compound 12, (E)-5-methoxy-2-(3-methoxybenzylidene)-2,3-dihydro-1H-inden-1-one, showed the best activity, further biological experiments, including RT-PCR analysis, quantitative real-time PCR, and inhibitory effects on IL-4-induced early growth response-1 (EGR-1) expression, EGR-1 DNA-binding activity, and IL-4-induced phosphorylation of the mitogen-activated protein kinase (MAPK) signaling cascade were performed. This study demonstrated that compound 12 acts on MAPK to block IL-4-triggered mRNA expression of TSLP via the MAPK-EGR-1 signaling pathway in HaCaT keratinocytes.